Law No. 21 Of The Year 2022 Amending Certain Provisions Of Law No. 120 Of The Year 1982 Promulgating The Law On Regulating The Commercial Agency Works And Certain Commercial Mediation Activities And The Law Attached Thereto = قانون رقم 21 لسنة 2022 بتعديل بعض أحكام القانون رقم 120 لسنة 1982 بإصدار قانون تنظيم أعمال الوكالة التجارية وبعض أعمال الوساطة التجارية والقانون المرافق له - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic